2011
DOI: 10.1124/dmd.111.038968
|View full text |Cite
|
Sign up to set email alerts
|

Culture Period-Dependent Changes in the Uptake of Transporter Substrates in Sandwich-Cultured Rat and Human Hepatocytes

Abstract: ABSTRACT:Sandwich-cultured hepatocytes (SCH) are a useful tool for evaluating hepatobiliary drug transport in vitro. Some studies have investigated the in vitro-in vivo correlations of the biliary clearance of drugs using SCH. In most cases, the biliary clearance observed in vivo correlated well with the predicted clearance, but the predicted absolute values were underestimated when based on in vitro experiments with SCH. We hypothesized that the down-regulated function of uptake transporters is one of the cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 39 publications
3
50
0
Order By: Relevance
“…Namely, OATP expression and function in rat SCH is decreased by 4-to 5-fold over days in culture (Kotani et al, 2011;Tchaparian et al, 2011). Therefore, RSV CL Uptake likely is underestimated in rat SCH (Table 1); in contrast, OATP-mediated CL Uptake in human SCH appears to be maintained over days in culture (Kotani et al, 2011). Bcrp and Mrp2 expression have been reported to increase and decrease, respectively, in rat SCH compared with liver tissue (Li et al, 2009a(Li et al, ,b, 2010.…”
Section: Hepatic Basolateral Efflux Of Rosuvastatinmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, OATP expression and function in rat SCH is decreased by 4-to 5-fold over days in culture (Kotani et al, 2011;Tchaparian et al, 2011). Therefore, RSV CL Uptake likely is underestimated in rat SCH (Table 1); in contrast, OATP-mediated CL Uptake in human SCH appears to be maintained over days in culture (Kotani et al, 2011). Bcrp and Mrp2 expression have been reported to increase and decrease, respectively, in rat SCH compared with liver tissue (Li et al, 2009a(Li et al, ,b, 2010.…”
Section: Hepatic Basolateral Efflux Of Rosuvastatinmentioning
confidence: 99%
“…Transporter expression and function have been reported to change over time in rat SCH. Namely, OATP expression and function in rat SCH is decreased by 4-to 5-fold over days in culture (Kotani et al, 2011;Tchaparian et al, 2011). Therefore, RSV CL Uptake likely is underestimated in rat SCH (Table 1); in contrast, OATP-mediated CL Uptake in human SCH appears to be maintained over days in culture (Kotani et al, 2011).…”
Section: Hepatic Basolateral Efflux Of Rosuvastatinmentioning
confidence: 99%
“…SCH involves culturing primary hepatocytes between two layers of gelled matrix in a sandwich configuration, allowing the hepatocytes to form a bile canalicular network (Bi et al, 2006). While down-regulation of uptake transporters in sandwichcultured rat hepatocytes has been a concern for the reliability of parameters obtained sandwich-cultured human hepatocytes (SCHH) has proven to maintain the expression of both transporters and major CYP enzymes Kimoto et al, 2011;Kotani et al, 2011). This model can be used to estimate the initial hepatic uptake and biliary secretion .…”
Section: Predicting Clearancementioning
confidence: 99%
“…These procedures are difficult, uncommon, and variable. In vitro predictions can be carried out in sandwichcultured rat or human hepatocytes, which preserve cell polarity and bile canaliculi (15,16), but uptake transporter expression is not well preserved in sandwich-cultured rat hepatocytes (17) and biliary clearance can be rate limited by uptake (18). Several studies have demonstrated that in vitro measures correlate with, but underpredict, in vivo biliary clearance (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%